Inovasi Gamis Terbaru Dalam Mendukung Layanan Administrasi Guru PAI Di Kabupaten Bantul - Tomi; Suprapto (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The digitisation of educational administration is a strategic step in improving the efficiency and accuracy of public services, especially for teachers. This study aims to explore the innovation of the GAMIS TERBARU service as part of the transformation of PAI teacher administration services in Bantul Regency. The method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Informants in this study included SIAGA administrators, EMIS administrators, and the Head of the PAIS Section of the Bantul Regency Ministry of Religious Affairs Office, as well as one PAI teacher in Bantul Regency. The results of the study show that GAMIS TERBARU provides easy access, time efficiency, and improves the accuracy of teacher administration data management. This innovation is considered effective because it is flexible and based on online communication media, making it easier for teachers to complete various administrative tasks without space and time constraints. However, its implementation still faces obstacles such as limited digital literacy, uneven internet coverage, and the absence of national standard regulations. This study recommends the need to strengthen human resources and policies so that similar innovations can be implemented sustainably and standardised.